Les médecins prestataires à la première ligne des soins dans la ville de Kisangani en République Démocratique du Congo : vers une typologie - Samuel I. Bosongo; Faustin C. Mukalenge; Albert M. Tambwe; Bart Criel (AOSIS, 2021)
The first-line physicians' practice in Kisangani city in Democratic Republic of Congo: Towards a typology. Background: In the Democratic Republic of the Congo (DRC), for a number of years, there has been a spontaneous and growing phenomenon of physicians operating at the front line of the health system, while this role is traditionally devolved to nurse-practitioners. This phenomenon does not align with the current health policy. Aim: The aim of this paper is to develop and discuss the main types of frontline physicians in the city of Kisangani. Setting: We conducted a descriptive cross-sectional study in two urban districts in the city of Kisangani. Methods: The study population consisted of all first-line health facilities that employed at least one physician. The construction of a typology of first-line physicians consisted of three stages: identification and definition of relevant dimensions of analysis; grouping cases based on empirical data; and analysis of significant relationships and establishment of the typology itself. Results: An involvement of physicians in healthcare delivery at the first line was observed in 60% of all first line facilities in the two urban districts. Two main types of first-line physicians were identified: firstly, and by large the most prevalent one (96% of cases), the 'hospital-like physician', and secondly, the much less frequent type of the 'supervision physician'. Conclusion: The involvement of physicians in first line healthcare is today a growing phenomenon in the DRC, especially in urban areas. The most dominant expression of this phenomenon is a transposition of the hospital-based physician model to the first line healthcare services, which thereby jeopardizing the specificity of first line healthcare.